Egypt Policy Note on Public Land Acquisition and Institutional Reforms : Application of Eminent Domain Principles - World Bank (Washington, DC, 2017)
This reports on the cost of doing business in Egypt consistently identify delays in land acquisition as one of the impediments to setting up new businesses as well as attracting foreign direct investments. Despite the provisions of Law 10/1990 (hereafter referred to as Law 10), which lays out a legal framework for the expropriation of real estate for public-interest projects, these delays persist due to overlapping in national and sectoral policies and practices. This Policy note acknowledges the absence of a comprehensive land administration system in Egypt. It focuses instead on the challenges facing land acquisition for public interest projects and theshortcomings of Law 10. It summarizes key challenges based on the findings of key research productsfrom the technical assistance (TA) program offered by the World Bank to the Egyptian government concerning land acquisition and policy reform, including the diagnostic analysis report prepared in June 2016 and the report of the TA Committee Members’ visit to India prepared in May 2016. The key challenges discussed in this policy note fall under two broad kinds: limitations in law, and policy coherence. To help develop a more coherent and transparent approach to land acquisition, this note also lays out recommendations and a road map. The Annex to this note highlights the broader issues of land administration, with a special focus on the weak institutionalization of deeds and title registration systems.